The Effects to GM-CSF Expression and Fibroblast Proliferation of pGM-CSF Containing Chitosan/PVP Hydrogels - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2016)
The aim of this study was to develop pGM-CSF containing chitosan/PVP hydrogel system for gene delivery. The hydrogels in semi-interpenetrating polymer network (semi-IPN) structure were synthesized by glutaraldehyde crosslinking between 2% chitosan and 2%, % 4, % 6 PVP. The viscosity, swelling properties and surface morphology of hydrogels were examined. These hydrogels showed highly porous structure. The porosity was increased with enhanced PVP concentration. Viscosity decreased with increasing PVP concentration of the hydrogels. The swelling percentage increased with increasing PVP concentration. In order to examine the effect of cell attachment and proliferation of hydrogels, NIH-3T3 fibroblast cell was used. The cells were able to attach on the top surface of hydrogels. However, the attachment of cells were slow at days 1 and 3. At days 7 and 14, cells looked healthy and normal and proliferated around and top of the hydrogels. With the ELISA study, the highest GM-CSF expression was obtained with pGM-CSF containing 2% chitosan+4% PVP hydrogels. MTT assay showed that chitosan/PVP hydrogels did not induce significant cytotoxic effect. As a result, these hydrogels could be served candidate for local gene delivery in tissue regeneration.
Keywords: pGM-CSF; chitosan; PVP; hydrogel; gene delivery; DRUG-DELIVERY; DNA DELIVERY; PLASMID DNA; PVP; MEMBRANES; RELEASE; SYSTEM